2011
DOI: 10.2116/analsci.27.1217
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of a Chrysotile Asbestos-containing Standard Material for Validating X-Ray Diffractometric Quantitation

Abstract: A standard material containing chrysotile asbestos for the validation of x-ray diffractometric quantitation was developed using an asbestos-containing building material i.e., perlite board. The board as the base material was crushed, pulverized, and homogenized. The homogeneity of the powder of perlite board was estimated by analysis of variance. The diffraction intensity values of the crystalline phases and the concentrations of elements determined by x-ray diffractometry and x-ray fluorescence analysis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…geological samples composed of various minerals). For example, glass beads have been prepared for the analyses of rocks, soils, pottery, and perlite board . As an example, Nakayama et al .…”
Section: Glass Beadsmentioning
confidence: 99%
“…geological samples composed of various minerals). For example, glass beads have been prepared for the analyses of rocks, soils, pottery, and perlite board . As an example, Nakayama et al .…”
Section: Glass Beadsmentioning
confidence: 99%
“…The crystalline purities of all the chemical reagents were determined by powder XRD/Rietveld refinement, and each diffraction intensity was corrected by the crystalline purities according to a previously reported method. 20,21) For example, the crystalline purities were measured as follows: hematite, 98.7%; magnetite, 94.0%; and eskolaite, 92.3%.…”
Section: Reagents For Standardsmentioning
confidence: 99%
“…These results indicate that eskolaite is the most suitable internal standard material for the XRD analysis of sintered ore. Asahi et al 20,21) reported that the mass absorption coefficient of an internal standard should be close to that of the analyte. The mass absorption coefficient of eskolaite (177 cm 2 .…”
Section: Selection Of the Internal Standard Materialsmentioning
confidence: 99%
“…These methods yield the analysis of the total carbon in cast iron; however, they do not allow the separative analysis of graphite and its polymorphism. X-ray diffractometry, which is used for the analysis of crystalline materials, such as zinc oxide, 18) asbestos, 19) calcium sulfate in air particles, 20) cement, 21) refractory materials, 22) and sintered ore 23) can be used to distinguish the analysis of different crystal phases of graphite and its polymorphism. Therefore, we propose a method to easily provide separative determination for different types of graphite by X-ray diffraction (XRD).…”
Section: Introductionmentioning
confidence: 99%